The Tax Effects of Inflation: Depreciation, Debt, and Miller's Equilibrium Tax Rates - Maher, Michael W.; Nantell, Timothy J. (Journal of Accounting Research, 1983)
Indexing historical cost accounting to has received considerable attention in the accounting literature. From a tax perspective, it is often argued that with historical cost accounting, increases effective corporate tax rates, ceteris paribus. (See Davidson and Weil [1978], Williams [1979], Bernard [1981], and Gonedes [1981].)1 A major reason is the failure of historical cost accounting to index the depreciation tax shield to inflation. But explicit indexation may not be necessary to achieve all the effects of indexation. The same effects can be attained, at least with respect to expected rates of inflation, if nominal interest rates incorporate unbiased forecasts of rates of inflation (Gonedes [1981, p. 247]).2 Davidson and Weil [1976] note that price-level adjusting the tax system would increase the depreciation tax shield, but it ... would diminish the tax-saving attribute of debt financing in a period of rising prices [1976, p. 99].